Functional analysis : surveys and recent results II : proceedings of the Conference on Functional Analysis, Paderborn, Germany, January 31 - February 4, 1979 - Bierstedt, Klaus-Dieter; Fuchssteiner, Benno (North-Holland mathematics studies ;, 1980)
Functional Analysis: Surveys and Recent Results II.